Performance analysis of volleyball clubs in the play-off stage of the "Wiener Stadtische" Serbian league in season 2015/2016 - Milic, V.; Mavric, F.; Memic, M.; Prelevic, A. (FIS communications in Physical Education, Sport and Recreation, 2016)
The aim of this scientific research paper is to carry out an analysis of the competitive activity and the statistical performance in the games of men volleyball teams that participated in the Serbian Volleyball League in season 2015/2016. The sample of this research consists of four men volleyball teams that have participated in the playoff stage of the competition called "WIENER STADTISCHE" Serbian Volleyball League and which have taken the last four places in the table at the end of the season. This research paper includes six games of the volleyball clubs Ribnica, Radnicki, Klek and In.ija i.e. their mutual matches in the play-off stage of the competition. The program Data-volley, designateby the International Volleyball Federation, was used for the variables of the technicaltactical dimension of the competitive activity structure. Statistical and analytical research method were used in this research. With the conducted research it was concluded that the efficiency coefficients and the results of technical and tactical activities have a high level of correlation with the final outcome of the match, but any individual element in volleyball that has the determining percentage performance statistics in the final outcome of the match should not be singled out.